Antihyperglycemic Activity of Piper crocatum Leaves and Cinnamomum burmannii Bark Mixture Extract in Streptozotocin-induced Diabetic Rats - Mega Safithri Hasibuan; Sedarnawati Yasni; Maria Bintang; Anna Setiadi Ranti (Institute for Research and Community Services (LPPM) ITB, 2016)
Indonesia presently has the fourth largest diabetic mellitus prevalence of all countries in the world. In a previous study, a mixture extract of Piper crocatum leaves and Cinnamomum burmannii bark showed in vitro antihyperglycemic activity. It acted as inhibitor of the a-glucosidase enzyme and had no toxic effect when it was administered orally to male and female rats for 28 days. In the present study, mixture extracts of P. crocatum leaves and C. burmannii bark were used to observe antihyperglycemic activity in diabetic rats induced with streptozotocin. Mixture extracts of P. crocatum leaves and C. burmannii bark were orally given to diabetic Sprague Dawley rats at various doses for 16 days. The results showed that the treatment led to a reduction of the blood glucose level, an increase in blood insulin level up to 170.75% at 1260 mg/kg body weight, maintaining the blood lipid level of the diabetic rats at a normal level, and an increase of pancreatic ÃŸ cells in the islets of Langerhans up to 2.2-fold at 1260 mg/kg body weight. The mixture extracts of P. crocatum and C. burmannii have antihyperglycemic activity, which enhances the number of pancreatic Î² cells.